Financial profitability of improved wheat seed storage at household level in some selected areas of Bangladesh (Bangladesh Journal of Agricultural Research, 2017)
Small and marginal farmers have little access to improved seed from institutional sources and are thus largely excluded from the benefits of new varieties. The production and storage of improved varieties seeds at the household (HH) level can overcome this problem. The study assessed the wheat seed storage systems used at HH level, with a particular emphasis on how the farmers are financially benefited by doing the seed storage business. The study analyzed data collected at random from Cereal Systems Initiative for South Asia in Bangladesh (CSISA-BD) project supported 210 farmers spread over three wheat growing Hubs namely Mymensingh, Faridpur and Rangpur. The study revealed that wheat growing farmers used different types of storage containers and showed the highest level of preference (score 7.2) on plastic/metal drum lining with polythene bag due to lower cost of storage, longevity, and seed quality maintenance. Wheat farmers retained on an average 95.7 kg of improved seed at household level. Majority of the retained seeds at HH level (64%) are being marketed and sold to neighbouring farmers, local markets, and dealers. Wheat seed storage at household level was a profitable business to most of the respondent farmers. They earned a reasonable net income (Tk.420-Tk.1471) from seed storage. The farmers who stored seed in plastic sac+poly bag received the highest net income (Tk.1471) due to less storage cost, and higher seed price. Respondent farmers did not face any critical problem during seed storageBangladesh J. Agril. Res. 42(2): 289-299, June 2017